Prognostic value of nine inflammatory biomarkers for critically ill patients with rheumatic heart disease: a retrospective study - Zhang, Ying; Ni, Xiaofei (Frontiers in Immunology, 2025)
BackgroundAmong various inflammatory biomarkers, the prognostic value in critically ill patients with rheumatic heart disease (RHD) remains unclear. This study aimed to compare the prognostic value of different inflammatory biomarkers in patients with RHD.MethodsThis study identified critically ill patients admitted to the intensive care unit from the Medical Information Mart for Intensive Care IV database (MIMIC-IV). Nine systemic inflammatory biomarkers, derived from various combinations of neutrophils, lymphocytes, monocytes, and platelets, were evaluated for their association with 30-day all-cause mortality. Receiver operating characteristic curve analysis was performed to identify the most predictive biomarker. Furthermore, Cox proportional hazards regression and restricted cubic spline analysis were employed to evaluate the association between the optimal biomarker and survival outcomes.ResultsA total of 1002 patients with RHD were included. Eight inflammatory biomarkers were predictive for 30-day all-cause mortality and the platelet-to-lymphocyte ratio (PLR) demonstrated the highest area under the curve value of 0.794 among these biomarkers. Then patients were divided into tertiles based on PLR. Multivariate Cox proportional hazards analysis demonstrated that an elevated PLR was significantly associated with increased 30-day all-cause mortality. After adjustment for potential confounders, elevated PLR remained an independent predictor of mortality (adjusted hazard ratio: 2.53; 95% confidence interval: 1.87–3.42; p < 0.001). Furthermore, restricted cubic spline analysis revealed a progressively increasing risk of all-cause mortality with higher PLR levels.ConclusionThese findings indicate that the PLR may be a useful indicator for evaluating the severity and guiding the treatment of RDH patients.